Scalability Terminology: Farms, Clones, Partitions, and Packs: RACS and RAPS - Devlin, Bill; Gray, Jim; Laing, Bill; Spix, George (1999)
Server systems must be able to start small and grow as demand increases. Internet-based eCommerce has made system growth more rapid and dynamic. Application Service Providers that consolidate application processing into large sites must also need dynamic growth. These sites grow by scale up, replacing servers with larger servers, or they grow by scale out adding extra servers. The scale out approach gives the slogans buying computing by the slice and building systems from CyberBricks: the brick or slice is the fundamental building block.